Design and implementation of a web-based online database of the U.P. Diliman Main Library's Index to Philippine Newspaper - Angeles, Chito N., 1976- (2006)
Applied research has not been a very popular type of research in the field of Library and Information Science (LIS). In general, most of the studies done in the field have been limited to basic researches. While basic research provides useful theories that can be applied to library processes, it does not produce viable applications. In this era, known as the "information age", when new models of digital services are being introduced in research libraries, the need to translate broad applications in mind into useful products and services is deemed high. Hence, in this study, the author went beyond simply generating new knowledge-but of producing an artifact. Specifically, the study aimed at developing a web-based online database of the University of the Philippines (U.P.) Diliman Main Library's Index to Philippine Newspapers (IPN). Using a traditional approach to systems development, the author employed the Systems Development Life Cycle (SDLC) model as its framework. Moreover, in determining system requirements and gathering pertinent information, the following methods were used: traditional administering of questionnaires; Joint Application Design (JAD); and document analysis and data structure analysis. The survey questionnaire was used to determine the library users and staff's needs and preferences for an online newspaper index database. A total of 113 respondents were surveyed for six days. On the other hand, Joint Application Design (JAD) was used to collect system requirements simultaneously from the key people involved with the system under study. Process models, in the form of Data Flow Diagrams (DFDs) were used to represent processes in the current and proposed system. Lastly, analysis of organizational documents, existing database structure, and sample records was carried out to further enhance the examination of the current system and discover more details about its organizational activities. Results of the study revealed that library users and staff prefer to have the Index to Philippine Newspapers accessible online and that there is a strong need for the library staff to automate the processes engaged in by the Filipiniana Serials, Media Services, and Computer Services sections with regard to the management, processing , servicing=, and retrieval of newspaper collection and the newspaper indexes which were successfully addressed by the new system. As a summary of implementation, a total of 161, 395 records of indexed articles from 22,081 issues in 9 newspaper titles were successfully converted to the new online database. In addition, 96,322 subject/name headings were generated from the existing records to build the authority list integrated into the new system. Finally, the new online system was successfully implemented using Free Open-Source Software (FOSS) and was made available thru the U.P. Diliman University Library's web site with the URL:http://www.mainlib.upd.edu.ph/ipn/.
Vita.
Thesis (M.L.I.S. Library & Information Science )--University of the Philippines Diliman.
Keywords: Online databases -- Philippines -- Quezon City; Index to Philippine Newspapers; Newspapers -- Abstracting and indexing -- Philippines -- Quezon City